1997
DOI: 10.1044/jslhr.4003.508
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Account of the Effect of Otitis Media on 15-Month-Olds' Categorization and Some Implications for Early Language Learning

Abstract: In the present study, 24 infants 14 to 16 months old (M = 15.3 months) with a history of otitis media (OM) and tube placement were tested for categorical responding within a visual familiarization-discrimination paradigm (cf. Roberts & Jacob, 1991; Roberts, 1995a). Sixteen infants were, on average, 4.6 months post-tubes. At the time of testing, hearing was reported to be normal. During both the familiarization and testing phases, reiterant speech ulterances (e.g., "ti ti the sasasa," "bo bo the sasasa," "gu gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The present study is the first to document that children without continuous health insurance coverage are less likely to receive elective surgery, even though it might be medically indicated. Because otitis media may have long-term aural, cognitive, and motor development consequences, [45][46][47][48] children without continuous health insurance coverage may remain at a disadvantage because they do not have equal access to this common surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is the first to document that children without continuous health insurance coverage are less likely to receive elective surgery, even though it might be medically indicated. Because otitis media may have long-term aural, cognitive, and motor development consequences, [45][46][47][48] children without continuous health insurance coverage may remain at a disadvantage because they do not have equal access to this common surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Of the children with a hearing problem, 65% displayed signifi cant levels of loss in both ears; 54% evidenced conductive loss; 16% had sensorineural loss in one or both ears; and 8% displayed mixed losses. It was once believed that hearing loss in the mild-to-moderate range had little effect on language acquisition; however, research on otitis media in infants has shown that losses of this magnitude can negatively affect speech and language development (Friel-Patti & Finitzo, 1990;Mody, Schwartz, Gravel, & Ruben, 1999;Nittrouer, 1996;Roberts, 1997;Wallace, Gravel, McCarton, & Ruben, 1988). Given the other defi cits faced by children with Down syndrome, it is likely that recurrent hearing loss compromises their language learning environment and that greater degrees of hearing loss and/or extended periods of middle ear disease will be associated with poorer outcomes on speech and language measures.…”
Section: Hearing Lossmentioning
confidence: 99%
“…However, when productions are inaccurate, it is impossible to determine whether the source of the error is in production or in perception. Roberts (1997) reported on the diYculties infants with OME presented on the perceptual categorization of the article 'the' when this was embedded in novel utterances such as 'bo bo the sasasa' simulating linguistic forms such as 'this is the 1 noun'. Roberts argued that the hearing loss associated with OME may compromise the consistent perception of elements of low phonetic saliency, in this case the article 'the', and cause them to uctuate 'above and below some 'attentional threshold ' ( Roberts 1997: 508).…”
Section: Introductionmentioning
confidence: 99%